PELAKSANAAN PENYITAAN BARANG BUKTI YANG DILAKUKAN OLEH PENYIDIK POLRI DAN HAMBATANNYA YANG DIHADAPI SERTA UPAYA MENGATASINYA DI POLRES KUTAI KARTANEGARA - Moh. Mukhlis (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTProcess or procedure seizure of evidence in criminal cases is as follows: Before doing his job, then the officer or investigator is required to obtain a letter of permission from the chairman of the local District Court in exceptional circumstances, it is necessary and urgent; Showed his ID to the person from which the object was confiscated; Authorities commanded the man who controlled the object to be seized to be handed to him on or writings that come from the suspect, shown to him, his possessions or intended to be, or tools to commit crime; Showed the object to be seized on those where it was confiscated or his family and mark items can be witnessed by the village head or chairman of a neighborhood with two witnesses; Make the minutes of seizure, after read out and be dated, signed by the investigator, the person concerned or his family and two witnesses; Before objects or items seized were put in storage house objects confiscated countries, it must be noted in advance about the weight or amount according to their kind, traits and characteristics of the object, place, day and date of seizure, identity dirimana objects was seized then packaged, labeled and stamped lag office and signed by the investigator; For the sake of security as may be necessary to do a photo shoot in advance.Some of the obstacles encountered by investigators in foreclosure, among others: Evidence no longer intact or damaged; Evidence transferable to any other person; Evidence sign other entities; Evidence made bail at the Pawnshop; Evidence is lost can not be found. Attempts by investigators in overcoming these barriers include: If the evidence transferable to another person, then make D.P.O (List of People Search) or D.P.B (Search Item List) to send to the ranks of Polda; If the evidence entered by other units, then approached Dankesatuan where the evidence is located, by having someone to buy the exhibits in hopes of evidence may be out of the unity of the region and used as evidence; If the evidence mortgaged, then the police did seizure of evidence by the requesting approval of foreclosure to the District Court with the provisions of the District Court, the new pawnshops submit the evidence, although it should be an argument; If the evidence is missing is not found, then the investigator conducting investigations in T.K.P (The Genesis waiver); Looking for witnesses and suspects by collecting witnesses and suspects to seek the truth of the evidence no longer shaped like jewelry that has been melted by the buyer.